(untitled) (PerCursos, 2021)
Understood as a process of urban intervention aimed at recomposing the biosphere, regenerative urbanism is one of the most prominent themes in achieving resilience in urban environments today. The research that gave rise to this article intended to explore regenerative urbanism concept, in a holistic understanding, through the elaboration of a systematic review. As a preliminary result, we observed that this new intervention paradigm acts both to achieve urban sustainability as well as a sensitive reading and consideration of the preexisting city. Considering this, the article seeks fundamentals for constructing a reflective process in decision-making for urban renewal actions with aims of resilience to climate change impacts. By reflective process, we consider knowing the exact measure of what is possible to develop, in terms of ecological performance, in preexisting areas, in which identity must be respected. To this end, we carried out a broad theoretical review in order to both problematize regenerative urbanism in relation to preexistence and landscape, as well as to build a propositional path for the dilemmas established in this relationship. We systematized a synthesis of good practices and procedures based on the foundations and conceptual review taken from literature that approaches regenerative urbanism in relation to preexistence and genuine aspects of a place that must be respected.